1982
DOI: 10.3109/00016358209019805
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a partial bite raising splint on the occlusal face height:An x-ray cephalometric study in human adults

Abstract: 20 patients (18 - 50 years) with pathological attrition of upper and/or lower anterior teeth were treated, as a temporary measure, by means of a partial chrome-cobalt splint covering the palatal surfaces of the six upper front teeth. Tantalum implants to provide reference points were placed in the basal portion of upper and lower jaw bones. Lateral cephalometric radiographs were taken with and without the splint at the beginning of treatment and thereafter every two months till the difference between measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0
5

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(100 citation statements)
references
References 9 publications
3
92
0
5
Order By: Relevance
“…39 However, many of the restorations showed some degree of wear and it is possible that this contributed to the re-establishment of some posterior occlusal contacts. The mean time of 7 months compares well with other studies 16,39 using cast metal bite planes but differing recall intervals could influence this conclusion. Just over a third of the subjects did not achieve posterior contacts in the premolar region during the study period.…”
Section: Re-establishment Of the Posterior Occlusionsupporting
confidence: 74%
See 1 more Smart Citation
“…39 However, many of the restorations showed some degree of wear and it is possible that this contributed to the re-establishment of some posterior occlusal contacts. The mean time of 7 months compares well with other studies 16,39 using cast metal bite planes but differing recall intervals could influence this conclusion. Just over a third of the subjects did not achieve posterior contacts in the premolar region during the study period.…”
Section: Re-establishment Of the Posterior Occlusionsupporting
confidence: 74%
“…15 Analysis of a further 20 subjects concluded that space creation anteriorly was achieved by a combination of anterior intrusion and posterior eruption taking place between 6 to 14 months. [16][17][18] Difficulties with chewing and speaking were reported but treatment was otherwise well tolerated.…”
Section: And J a Goodmentioning
confidence: 99%
“…6 The authors reported a 100% success rate in achieving the desired interocclusal space in the subsequent 20 cases treated. The technique offered the obvious advantage in reducing the need to remove tooth tissue in order to accommodate any planned restorations.…”
Section: Introductionmentioning
confidence: 97%
“…However, when teeth wear, the alveolar bone and associated tissues adapt to some degree to change with alveolar compensation. 80 Despite losing crown height, teeth maintain their occlusal contact; this may lead to problems with respect to their reconstruction, because there is not enough space for the restorative material. To prevent an invasive, full-mouth rehabilitation, it can be beneficial to gain interocclusal space with orthodontic measures, especially if groups of teeth (for example, all the teeth in the anterior region) are involved in erosive tooth wear.…”
Section: Treatment Strategiesmentioning
confidence: 99%